Chromosome diversity in species of the genus Arachis, revealed by FISH and CMA/ DAPI banding, and inferences about their karyotype differentiation - Silvestri, María Celeste (2020)
Fil: Silvestri, María Celeste. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.